MODERN METHODS OF INVESTIGATION AGAINST FORGERY OF ELECTRONIC DOCUMENTS - Sabirova Muhabbat Akramovna (Western European Studies, 2024)
This article examines the main problems associated with forgery of electronic documents and the importance of implementing reliable investigative methods to solve this problem. It explores the various modern techniques and tools available to investigate the forgery of electronic documents, and by understanding and using these advanced investigative techniques, authorities and organizations can effectively protect the integrity and authenticity of electronic documents
Keywords: forgery; electronic documents; modern technologies